A Daunting Journey: Accessing a Lead Maternity Care Midwife - Priday, Adrienne Desley (Auckland University of Technology, 2019)
One outcome measure of quality maternity care is the rate of stillbirth and neonatal death. To enhance health outcomes for women and babies in New Zealand, the Ministry of Health and the Perinatal and Maternal Mortality Review Committee (PMMRC) recommend early engagement with maternity services. However, Counties Manukau Health region has a high rate of women accessing and engaging with maternity care after the first trimester of pregnancy and one of the highest rates of stillbirth and neonatal death in New Zealand. To improve engagement with maternity care, in 2012 Counties Manukau Health initiated a recommendation from a maternity service review to co-locate midwives alongside general practitioners’ clinics (GP clinic) in high socioeconomic deprivation communities. The initiative was intended to support women to access and engage with midwifery care before 10 weeks gestation. The aim of this interpretive descriptive study was to explore the experience of eight women accessing the services of midwives using this model of care, co-located with their GP clinic. In keeping with the interpretive descriptive methodology, one-to-one semi-structured interviews were undertaken and data was examined using thematic analysis. Two themes were identified from this study. ‘It’s a daunting journey accessing midwifery care’ and: ‘Circumventing the maternity health service maze’; These findings highlight the experience the women had accessing a Lead Maternity Care (LMC) midwife, the socio-cultural influences, the resource and service challenges. The findings revealed that a midwife recommendation combined with support from their GP or nurse assisted the women to access LMC care with confidence and ease. The findings may inform health policy makers, clinicians and others - including the people accessing maternity services.
Keywords: Accessing maternity care; Antenatal care; Pregnancy care in high deprivation communites; Lead Maternity Care; Finding midwifery care